Coming home to Minden Barracks: Historical site at Universiti Sains Malaysia (USM) - Mohamad, Radia Banu Jan; Fesal, Fujica Azura; Jan, Noor Azlinda Wan (2019)
The Minden Barracks was a military barracks located in the town of Gelugor in Northeast District of Penang Island, Malaysia. It was operational from 1939 to 1971 and the site has since been decommissioned to accommodate the main campus of Universiti Sains Malaysia (USM). It has been almost fifty years since the regiments left the place, however, the memories of staying in the area are still being reminisced by the residents, hence, representing a convergence of heritage tourism whereby travelling to the destination to experience the place and activities that realistically represent the stories and people of the past. This paper depicts the initiatives taken by the librarians from the Malaysiana and Archives Division of Universiti Sains Malaysia Library to learn about the historical background of the campus by tracking the information sharing of the previous residents of the barracks on the social media. It has led to an outcome of getting some information about how the place used to be and an organized event of Oral history with one of the former occupants who keep coming back to relive the memories of Minden Barracks, to feel the connection with the place, and to share stories and experiences of a place once called home to families and friends.